Research on drug drug interactions with metabolism and brand names with some uses - Akshay Kiran, Myle (Innovare Journal of Medical Sciences, 2017)
rug interactions are the harmful or beneficial effects of co administered medicinal products, these interaction may be synergistic or antogon istic pharmco kinetics or pharmaco dynamics, drug interactions exists between drugs anddrugs, drug and foods, drugs and herbs, benefits effects include convenience . Reduced toxicity and reduction. ANTIHISTIMINE, ANTIHISTIMINE, ASTHMA, ANALAGESIC, TYPHOID, HYPERTENSION, TUBERCULOSIS ANTIBIOTICS, FILARIA, RHEUMATOID ARTHRITIS, ANTIPYRITIC, ANTICANCER IMMUNOLOGICAL DISEASES, ECTOPIC PREGNANCY, FEVER, OSTEOARTHRITIS AND ANTIPYRITIC, ANALAGESIC, HIV AIDS, CHICKEN POX, SALICYLATE, PHENYTOIN, ESTROGENS, HMG COA REDUCTASE INHIBITORS, BARBITURATES, CHLORAMPHENICAL, ANTACIDS, ANTICOAGULANT. When two or more drugs are administered concurrently or within a reasonable time or after each other (both prescription drugs and non prescription drugs are involved) , the result may be in difference, synergisim, potentation, antagonisim this is called AS .DRUG-DRUG INTRACTION. Drug metabolism interactions results in the increase of biological half life or reduction of clearance there requiring lower doses, imipramine reduces the clearance of epinephrine, some examples of the drugs that inhibit metabolism like Erythromycin, ketocanazole, fluxetin, cimitidine, Allopurinol , carbamazepine, phenobarbital, Rifampacin , and phenytoin. Risk of Therapeutic failure, stoppage of induced may lead to toxic concentration of substrate and induction may lead to formation of toxic metabolites. Â